PENGARUH KOMPETENSI PEGAWAI, ETOS KERJA, FASILITAS KERJA DAN DISIPLIN KERJA TERHADAP PENGEMBANGAN PEGAWAI DI KANTOR WILAYAH DJP SUMATERA UTARA I - Muhammad Arkan Sahadat (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The formulation of the problem in this study are: Does Employee competence affect employee development in the North Sumatra I DGT Regional Office. Does work ethic affect employee development? Does work facilities affect employee development. Does work discipline affect employee development? Does employee competence, work ethic, work facilities and discipline simultaneously have a significant effect on employee development, Research Objectives Are:. The data analysis technique used is multiple linear regression analysis.The results showed that there was a significant influence between competencies on employee development, because according to the results of the analysis of t count t-table (2.753 1.67) at n = 56 with a significance level of 95%. There was a significant influence between work ethic on development employee, the results of analysis of arithmetic t-table (2.114 1.67) at n = 56 with a significance level of 95%. There is a significant influence between work facilities on employee development, because according to the results of analysis of arithmetic t-table (1,722 1.67) at n = 56 with a significance level of 95%. There is a significant influence between work Discipline on employee development, because according to the results of t analysis t-table (2.664 1.67) at n = 56 with a significance level of 95%. F-count value F table (103,996 2, 56) together (multiple) there is a positive and significant influence of employee competence, work ethic, work facilities and work discipline on employee development. Thus the hypothesis proposed is accepted.